2004
DOI: 10.1044/1058-0360(2004/026)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phonemic Perception Training on the Speech Production and Phonological Awareness Skills of Children With Expressive Phonological Delay

Abstract: Children with expressive phonological delays often possess poor underlying perceptual knowledge of the sound system and show delayed development of segmental organization of that system. The purpose of this study was to investigate the benefits of a perceptual approach to the treatment of expressive phonological delay. Thirty-four preschoolers with moderate or severe expressive phonological delays received 16 treatment sessions in addition to their regular speech-language therapy. The experimental group receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 56 publications
(70 reference statements)
3
57
0
8
Order By: Relevance
“…Furthermore, where group studies have been reported in the literature, the amount and intensity of therapy has been greater than the 8 sessions of direct SLP and 16 sessions of follow-up practice offered in this study (Almost & Rosenbaum, 1998;Bowen & Cupples, 1999;Rvachew, Nowak & Cloutier, 2004). In contrast, Denne, Langdown, Pring and Roy (2005) found that a group of children receiving 12 hours of phonological awareness therapy were no different from an untreated group in terms of speech production post-therapy.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, where group studies have been reported in the literature, the amount and intensity of therapy has been greater than the 8 sessions of direct SLP and 16 sessions of follow-up practice offered in this study (Almost & Rosenbaum, 1998;Bowen & Cupples, 1999;Rvachew, Nowak & Cloutier, 2004). In contrast, Denne, Langdown, Pring and Roy (2005) found that a group of children receiving 12 hours of phonological awareness therapy were no different from an untreated group in terms of speech production post-therapy.…”
Section: Discussionmentioning
confidence: 57%
“…This contradicts the various findings that speech perception alone aids the production of L2 sounds (Botero, 2012a;Bradlow et. al., 1997;Counselman, 2010;Rvachew et. al., 2004;Wang.…”
Section: Discussionmentioning
confidence: 99%
“…This fact may be reinforced by another study 22 , which states that the presence of positive results in relation to the phonemic discrimination of specific sounds can promote a greater progression of therapy, giving important considerations for the selection of target sounds, as well as for the type of treatment to be adopted. Moreover, the insertion of a perceptive training concomitant to phonological therapy is capable to offer improvements in the phoneme discrimination, as in speech patterns 23 . With respect to the instrument that was used in this study, it was also investigated a possible influence of the minimal pairs of the SVDT at the performance of the assessed children.…”
Section: Acknowledgmentsmentioning
confidence: 99%